Beyond the Surface - Anita Ravi; Linda Prine; Gabrielle deFiebre; Susan E. Rubin (SAGE Publishing, 2017)
Purpose: To describe rates of and reasons for follow-up among adolescents and adults receiving contraceptive implants in a Federally Qualified Health Center (FQHC). Methods: Retrospective comparison of patient-initiated implant-related contacts during the 6 months postinsertion among adolescents (110) and adults (154) who had implants placed at a FQHC network. Results: Forty percent of adolescents and 26% of adults initiated follow-up ( P = .016). Bleeding changes and discussing removal were the most common reasons for follow-up for both groups. Adolescents (5.5%) and adults (9.0%) had similar removal rates ( P = .348). However, among patients who discussed implant removal, adults were more likely to have removals compared with adolescents ( P = .002). Conclusions: Other FQHCs may anticipate a similar experience to ours, where adolescents may be more likely than adults to initiate implant-related follow up, with removal rates of less than 10% at 6 months. Further study of physician decision making and patient autonomy regarding implantable contraception removal requests is warranted.